2021
DOI: 10.3389/fphar.2021.691606
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Medicines for Children: A Systematic Review

Abstract: Background: Accessibility of medicines for children is a matter of global concern. Medicines prescribed for children are often off-label. To formulate appropriate policies and undertake necessary interventions to improve access to medicines for children, it is necessary to evaluate the accessibility of medicines for children. However, there is no systematic review of the medicine accessibility for children.Methods: Relevant studies were identified through searching Pubmed, Embase, CNKI, Wanfang, VIP, World Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
(28 reference statements)
4
17
0
1
Order By: Relevance
“…[2][3][4][5][6] Several studies have shown that low availability, high prices and poor affordability have kept medicines out of reach for children, as well as lack of age-appropriate formulations, adequate dosing and administration instructions in the product labelling. [7][8][9][10][11] Over many decades, paediatric drug development has been hindered by various factors. They include a common notion to protect children from research, little appreciation of paediatric pharmacology, recruitment challenges and low market pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Several studies have shown that low availability, high prices and poor affordability have kept medicines out of reach for children, as well as lack of age-appropriate formulations, adequate dosing and administration instructions in the product labelling. [7][8][9][10][11] Over many decades, paediatric drug development has been hindered by various factors. They include a common notion to protect children from research, little appreciation of paediatric pharmacology, recruitment challenges and low market pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the availability of medicines for children is low and this is a significant public health problem, whereby off‐label prescribing remains high 2–6 . Several studies have shown that low availability, high prices and poor affordability have kept medicines out of reach for children, as well as lack of age‐appropriate formulations, adequate dosing and administration instructions in the product labelling 7–11 …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a systematic review has identified 18 multicentre studies evaluating the accessibility of essential medicines for children ( Chen et al, 2021 ). The majority of studies used the WHO/HAI standardized methodology ( World Health Organization and Health Action International, 2008 ), which was jointly developed by WHO and HAI in 2000 for standardizing studies on the accessibility of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO/HAI standardized methodology estimates the accessibility of medicines by investigating medicine availability, price, and affordability. The results have shown that the availability of essential medicines for children is generally low in low-income and middle-income countries, the median price ratios of originator brands was higher than that of lowest-priced generics, and the most lowest-priced generics had better affordability ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trials in "average" patients aim to determine if a medicine will be safe and efficacious, but drugs are also required for patients that lie outside of the average, including paediatrics and older persons. Few drugs have undergone clinical trials in paediatric patients, so in the absence of specific formulations, physicians can opt to use such drugs off-label and/or in an unlicensed fashion (Chen et al, 2021). Off-label use is one when a licenced product is used outside the specifics of the license or label granted by the national regulator.…”
mentioning
confidence: 99%